Transport infrastructures and regional development: The discovery of centrality of the container terminal of Gioia Tauro in the Mediterranian - Francesco Latella; Domenico Marino; Francesco Timpano (European Regional Science Association (ERSA), 1998)
European container terminals of Mediterranean are enjoying of a discovery on the more dynamics routes of the whole world that link Europe to Far East-Pacific. This centrality consists in the acquisition of a relative advantage in terms of 6 -7 days less of navigation respect to big ports of call of North Europe. In this framework, the new installation of Gioia Tauro?s container terminal is demonstrating to be one of the most important junctions of transhipment of South Europe. This could manifest completely his potentialities in the same measures in which will be guided at the same time adequate territorial policies and lay the bases for logistic systems of high level. This means to direct in the national and continental hinterland the construction of a system of infrastructures of road and railway junctions necessarily adequate and advanced in terms of technician level and capacity of response. Only in this sense it will be possible to initiate a competition forms among economic systems in a territorial base rather than among single productive units. In fact, after a ten-year period of interventions for sectors, transeuropean network of transportation could start to considered as a first systematic tentative of integrated actions among transportation politics and regional politics of European Union. By starting, therefore, by a systemic approach, the paper turns to a simulation model and to specific inquiry on the field to gather the impacts of the container terminal to territorial level. The aim is to verify if and in which way the politics of national and community transport linked to the birth of container port of Gioia Tauro, will assume the features of a complex regional development politics able to mitigate and/or prevent the imbalances become worse in the ambit of European Union.
Keywords: 330